Empatia primaria e desiderio mimetico: limiti funzionali dei “neuroni-specchio” - Catarsi, Carlo (Studi sulla Formazione/Open Journal of Education, 2011)
According to a Gallese linear definition, a “mirror mechanism” is based on the evidence that neural structures active during sensations and emotions are active also when the same sensations and emotions are to be detected in others. In this remark is argued the thesis that this basic psychic disposition is not sufficient to explain the human orientation to the moral evaluation. This lack is deduced from effective relevance , within a moral complex choice, of mental representations of socio-cultural and political alternatives.